Brigitte Bardot in Roger Vadim's "... and God created woman" - Misraki, Paul 1908-1998 (Criterion Coll., 2000)
Juliette is an 18 year-old orphan whose unbridled appetite for pleasure shakes up all of St. Tropez. Her sweet but naïve husband Michel endures beatings, insults and mambo in his attempts to tame her wild ways.
Bildformat 2.35:1 (16:9) aspect ratio
Original: Frankreich, Italien 1956
Enth. new widescreen digital transfer, supervised and approved by Roger Vadim and enhanced for 16x9 televisions ; restoration demonstration
Keywords: Adultère - Films; Femmes - Sexualité - Films; Films de murs; Longs métrages - France; Mariage - Films; Relations entre hommes et femmes - Films; Frau; Adultery -- Drama; Man-woman relationships -- Drama; Marriage -- Drama; Women -- Sexual behavior -- Drama; Feature films; Motion pictures, French